Fostering Institutions to Contain Corruption - Diamond, Larry (World Bank, Washington, DC, 2012)
Corruption can never be completely or permanently eliminated. The question is, how can it be controlled? How can a country move from a situation where corruption may be the norm to a situation where corruption is morally intolerable and behaviorally rare? To control corruption, the expected costs of engaging in corruption must be dramatically increased. Public officals must perceive a substantial risk that if they engage in corrupt conduct they will lose their offices, forfeit illegally acquired wealth, and even go to prison. Implementing such sanctions aganist corruption requires an institutional framework to control corruption. Effective and durable corruption control requires multiple, reinforcing, and overlapping institutions of accountability. Where corruption is endemic, these institutions need to be of three kinds: horizontal accountability, vertical accountability, and external accountability. The primary institutions of horizontal accountability are the law, anti-corruption bodies, the ombudsman's office, public audits, and the judicial system. Institutions of vertical accountability include an independent electoral commission, independent mass media, and nongovernmental organizations. External accountability encompasses extensive international scrutiny and support.